2023
DOI: 10.1101/2023.01.23.523684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correcting dilated cardiomyopathy with fibroblast-targeted p38 deficiency

Abstract: Inherited mutations in contractile and structural genes, which decrease cardiomyocyte tension generation, are principal drivers of dilated cardiomyopathy (DCM) - the leading cause of heart failure. Progress towards developing precision therapeutics for and defining the underlying determinants of DCM has been cardiomyocyte centric with negligible attention directed towards fibroblasts despite their role in regulating the best predictor of DCM severity, cardiac fibrosis. Given that failure to reverse fibrosis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…However, some studies have suggested that broblast activity may not be directly correlated with cardiac brosis in DCM. Bretherton et al [19] reported that studies on precision therapeutics and the etiological factors of DCM have predominantly focused on cardiomyocytes with minimal emphasis on broblasts despite their crucial role in modulating cardiac brosis, a key indicator of DCM severity. Modifying broblast activity can markedly enhance cardiomyocyte contractile function and myocardial remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have suggested that broblast activity may not be directly correlated with cardiac brosis in DCM. Bretherton et al [19] reported that studies on precision therapeutics and the etiological factors of DCM have predominantly focused on cardiomyocytes with minimal emphasis on broblasts despite their crucial role in modulating cardiac brosis, a key indicator of DCM severity. Modifying broblast activity can markedly enhance cardiomyocyte contractile function and myocardial remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…A question relating to the therapeutic efficacy of OM and other myosin activators is whether their use not only increases tension in DCM but also reduces fibrosis. [4,112]. This is an important issue as fibrosis has been known for some time to be a predictor of mortality and hospitalization in DCM [1,113,114].…”
Section: Myosin Heavy Chain As a Drug Targetmentioning
confidence: 99%
“…This is an important issue as fibrosis has been known for some time to be a predictor of mortality and hospitalization in DCM [1,113,114]. In view of lack of evidence that myosin activators reverse fibrosis in systolic HF, it has been argued that a fibroblast specific therapeutic approach is necessary [4]. This make sense as fibroblast proliferation occurs with an avoidance of cell death Even so the per cent of patients with mid-wall fibrosis, the most common manifestation, is less than half the population.…”
Section: Myosin Heavy Chain As a Drug Targetmentioning
confidence: 99%
See 2 more Smart Citations